Learning from our own lessons: pre-service teachers' narratives of teaching as an experiment. Issue 1 (1st January 2018) - Wickstrom, Megan H.; Wilm, Stephanie; Mills, Emily; Johnson, Alexis; Leonard, Nicole; Larberg, Raegan
Abstract: Pre-service teachers need to develop habits of mind that allow them to grow as new teachers. This article describes an elementary mathematics methods course in which teaching as an experiment was used a framework for pre-service teachers to participate in action research by developing learning goals, observing and analyzing student thinking, hypothesizing and enacting teaching strategies, and reflecting on the effectiveness of a lesson. Through analysis of reflections and lesson plans, the article explores three groups of pre-service teachers' reflections on teaching as well as their confidence across the semester. By treating lessons as experiments, the pre-service teachers were able to develop appropriate teaching responses over time as well as gain confidence in their abilities.